2000
DOI: 10.1046/j.1440-1754.2000.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and associated psychopathology in young people with intellectual disability

Abstract: The results suggest that epilepsy has little or no influence on problem behaviours for young people with ID. Our attempt to understand the pathogenesis of behaviour problems in persons with ID may be better directed towards understanding genetic mechanisms than epilepsy pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…This is considered to reflect some underlying organic cause associated with more severe levels of intellectual disability (Lewis et al, 2000;Murphy et al, 1998).…”
mentioning
confidence: 99%
“…This is considered to reflect some underlying organic cause associated with more severe levels of intellectual disability (Lewis et al, 2000;Murphy et al, 1998).…”
mentioning
confidence: 99%
“…Lewis et al (2000) studied children with low IQ to determine whether those who also had epilepsy were doing worse. Although results did not reach statistical significance, children who had active epilepsy had the highest total behavior problem scores (Lewis et al 2000). In a study by Sabaz et al (2001), 65% of the children with both low IQ and epilepsy scored in the clinically abnormal range compared with 41% of those with mental retardation alone.…”
mentioning
confidence: 99%
“…Goulden et al (18) documented prevalence of mental retardation of pre‐ or perinatal etiology in 28 to 38% of children with epilepsy. Despite this high prevalence rate, minimal research has specifically addressed the impact of epilepsy with coexisting ID on HRQOL in children (19,20). This research has shown conflicting results due to differences in control groups, psychosocial instruments used, and methodologic problems in classification of epilepsy syndrome and evaluation of seizure severity.…”
mentioning
confidence: 99%